Overthinking Pada Mahasiswa: Analisis Perbandingan Mahasiswa Tingkat Awal dan Tingkat Akhir - Ivanka, Dea; Dinata Saragi, Muhammad Putra (Universitas Muhammadiyah Metro, 2023)
This study aimed at overthinking in early and final-year students from UINSU and non-UINSU students. This research approach is a mixed method (Mixed Quantitative and Qualitative Methods). Both approaches are descriptive. Quantitative research, in the process of collecting data by distributing questionnaires online using the Google form and distributed from 12-20 February 2023. The results of distributing the online questionnaires were 200 respondents. Two measurement scales are used in descriptive quantitative research, namely